2020
DOI: 10.3389/fpsyg.2019.03016
|View full text |Cite
|
Sign up to set email alerts
|

School Incivility and Academic Burnout: The Mediating Role of Perceived Peer Support and the Moderating Role of Future Academic Self-Salience

Abstract: This study examined a mediation model about whether perceived peer support (PPS) mediates the link between school incivility and academic burnout. More importantly, we also investigated how future academic self-salience (FASS) as a trait moderates this mediated relationship. We collected data from a sample of 475 students by a two-wave survey. Results indicate that PPS mediated the relationships for school incivility with academic burnout. Moderated mediation analysis intended to further reveal that PPS mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 34 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…The presence of school burnout can lead to development of affective and cognitive symptoms, such as disrespectful, negative attitudes toward other students, the school and life in general ( Aypay, 2017 , Bai et al, 2020 ). For example, in university students, cynicism has been found to correlate negatively with support for sociocultural values and norms ( Jia et al, 2009 ).…”
mentioning
confidence: 99%
“…The presence of school burnout can lead to development of affective and cognitive symptoms, such as disrespectful, negative attitudes toward other students, the school and life in general ( Aypay, 2017 , Bai et al, 2020 ). For example, in university students, cynicism has been found to correlate negatively with support for sociocultural values and norms ( Jia et al, 2009 ).…”
mentioning
confidence: 99%
“…Students participate in extra foreign language learning after school or on off days in addition to the usual intracurriculum foreign language learning (Bai et al, 2020). This also create academic pressure to do well and act admirably to meet the expectations of their signi cant others and preserve their sense of self (Prior & Gollan, 2011).…”
Section: Insert Table VI Here 4 Discussionmentioning
confidence: 99%
“…High peer support might motivated students to actively cope when learning difficulties arise, so they felt less burn-out [15]. Bai et al also found that peer support was negatively correlated with academic burn-out, and adolescents who have experienced uncivilized behaviors in school were more likely to have a higher degree of academic burn-out [23].…”
Section: External Factorsmentioning
confidence: 99%